STUDI JENIS DAN POLA SEBARAN TUMBUHAN LAMUN DI PERAIRAN DESA TELUK BULI KECAMATAN MABA - Abdullah, Sirajuddin; Tolangara, Abdulrasyid; Ahmad, Hasna (UNIVERSITAS KHAIRUN, 2023)
Seagrass meadows are ecosystems consisting of one or more species of seagrass interacting with biotic and abiotic factors in their environment. Ecologically, seagrass has several important functions in coastal areas, one of which is seagrass as a primary producer in shallow waters which is a food source for several types of organisms. This research aims to find out the types of seagrass plants in the waters of Teluk Buli Village, and find out the pattern of seagrass plant distribution, and find out what environmental factors affect the growth of seagrass plants. This type of research is descriptive explorative, where the data collected includes the types of seagrass plants that have been identified, the pattern of seagrass plant distribution, and environmental factors that affect the distribution pattern of seagrass plants. The method used for data collection is the quadratic method (calculated plot). Analysis of seagrass plant type data using seagrass plant identification manuals, seagrass plant distribution patterns using morista spread index formulas, and environmental factors that affect the pattern of seagrass plant distribution are described and contained in observation tables. The results showed that the type of seagrass plant found in the waters of Teluk Buli Village was a type of Enhalus acoroides. The results of the calculation of the morista spread index showed that the seagrass plant Enhalus acoroides had a clustered distribution pattern with a value of Id 1. The results of measuring the environmental parameters of seagrass plants in the waters of Teluk Buli village, namely pH 5-6.6 categorized as acid, Humidity 20%-50%, and Salinity 28% - 31% Optimum category.